Photonics Society of Poland celebrates 15th Anniversary - Woliński, Tomasz (Photonics Letters of Poland, 2023)
Photonics Society of Poland (PSP) celebrated its 15th Anniversary on 12 May 2023 in the Physics Building of the Warsaw University of Technology. The Jubilee PSP Symposium was co-located with the 2nd International Photonics Job Fair and with the International Day of Light IDL-2023. The current, 58th PLP issue contains - among others - papers written by the distinguished guests of 15th Anniversary PSP Jubilee: Bernard Kress, Ulrike Woggon, and Claus Roll.